Skeletal Muscle Function, Structure, and Metabolism in Patients With Heart Failure With Reduced Ejection Fraction and Heart Failure With Preserved Ejection Fraction. (December 2020) - Bekfani, Tarek; Bekhite Elsaied, Mohamed; Derlien, Steffen; Nisser, Jenny; Westermann, Martin; Nietzsche, Sandor; Hamadanchi, Ali; Fröb, Elisabeth; Westphal, Julian; Haase, Daniela; Kretzschmar, Tom; Schlattmann, Peter; et al.
Abstract : Background: Reduced exercise capacity in patients with heart failure (HF) could be partially explained by skeletal muscle dysfunction. We compared skeletal muscle function, structure, and metabolism among clinically stable outpatients with HF with preserved ejection fraction, HF with reduced ejection fraction, and healthy controls (HC). Furthermore, the molecular, metabolic, and clinical profile of patients with reduced muscle endurance was described. Methods: Fifty-five participants were recruited prospectively at the University Hospital Jena (17 HF with preserved ejection fraction, 18 HF with reduced ejection fraction, and 20 HC). All participants underwent echocardiography, cardiopulmonary exercise testing, 6-minute walking test, isokinetic muscle function, and skeletal muscle biopsies. Expression levels of fatty acid oxidation, glucose metabolism, atrophy genes, and proteins as well as inflammatory biomarkers were assessed. Mitochondria were evaluated using electron microscopy. Results: Patients with HF with preserved ejection fraction showed compared with HF with reduced ejection fraction and HC reduced muscle strength (eccentric extension: 13.3±5.0 versus 18.0±5.9 versus 17.9±5.1 Nm/kg, P =0.04), elevated levels of MSTN-2 (myostatin-2), FBXO-32 (F-box only protein 32 [Atrogin1]) gene and protein, and smaller mitochondrial size ( P <0.05). Mitochondrial function and fatty acid and glucose metabolism were impaired in HF-patients compared with HC ( P <0.05). In a multiple regression analysis, GDF-15 (growth and differentiation factor 15), CPT1B (carnitine palmitoyltransferase IB)-protein and oral anticoagulation were independent factors for predicting reduced muscle endurance after adjusting for age (log10 GDF-15 [pg/mL] [B, −54.3 (95% CI, −106 to −2.00), P =0.043], log10 CPT1B per fold increase [B, 49.3 (95% CI, 1.90–96.77), P =0.042]; oral anticoagulation present [B, 44.8 (95% CI, 27.90–61.78), P <0.001]). Conclusions: Patients with HF with preserved ejection fraction have worse muscle function and predominant muscle atrophy compared with those with HF with reduced ejection fraction and HC. Inflammatory biomarkers, fatty acid oxidation, and oral anticoagulation were independent factors for predicting reduced muscle endurance. Abstract : Supplemental Digital Content is available in the text.